Eryptosis in renal anemia: mechanisms, clinical implications, and therapeutic targeting - Deng, Xiang; Gong, Xiangyu; Huang, Yi; Zhou, Jie; Ren, Sichong (Frontiers in Pharmacology, 2025)
Renal anemia is one of the most common complications of chronic kidney disease (CKD) and is associated with serious clinical consequences. Its prevalence increases significantly as renal function declines, affecting over 90% of dialysis patients. Traditionally, the pathophysiology of renal anemia has been centered on two primary mechanisms: absolute or relative deficiency of erythropoietin (EPO) and disorders of iron metabolism. However, even with treatment using erythropoiesis-stimulating agents (ESAs) and iron supplements, approximately half of the patients exhibit a hypo-responsive or suboptimal correction of anemia, suggesting the involvement of other significant mechanisms in the development and progression of renal anemia. In recent years, eryptosis, a novel mechanism, has garnered increasing attention. Eryptosis is a form of programmed cell death specific to erythrocytes, sharing similarities with but distinct from apoptosis in nucleated cells. It is characterized by cell shrinkage, membrane blebbing, and phosphatidylserine (PS) externalization. In the CKD milieu, various uremic toxins, oxidative stress, and inflammatory factors can accelerate the eryptosis process, leading to a significant reduction in red blood cell lifespan—from the normal 120 days toonly 60–90 days in CKD patients. This accelerated eryptosis represents a major contributing factor to renal anemia. This review aims to systematically summarize the association between renal anemia and eryptosis, providing an in-depth exploration of its molecular mechanisms, clinical implications, and therapeutic potential. Distinguishing itself from existing reviews, this article will focus on the central role of eryptosis in renal anemia. It integrates the latest evidence from basic research and clinical data to propose innovative therapeutic strategies targeting eryptosis, thereby offering new perspectives for improving the current management of renal anemia.